Oil Trading Products and Economic Growth in Nigeria: A Disaggregated Case (Journal of Management and Social Sciences, 2022)
The impact of crude oil trade on economic growth has sustained a lasting debate on the Nigerian economic stage given the relevance of oil in the revenue generation capacity of the country since the advent of oil. This study examines the impact of crude oil traded goods on economic growth using annual data from 1986-2019. The study adopts the Error correction model (ECM) technique and the empirical findings from the ECM indicate that importation of automotive gas oil was significant and negatively related to economic growth in Nigeria. On the contrary, premium motor spirit import impacts economic growth positively and quite significantly in the period under review. Other variables-dual purpose kerosene and liquefied petroleum gas are also revealed to have negative and positive relationship on economic growth in Nigeria respectively, though not significant at 5% significant level. Similarly, the study further finds that oil export exhibits a hugely significant impact on economic growth in Nigeria in the period under study. Based on these findings, we recommend among others that: the Nigerian government should revamp the existing refineries to encourage domestic production to meet up with the domestic demand for petroleum products, especially for PMS. We also recommend the diversification of the economy into other oil products as well as addressing the twin issues of oil theft and insecurity in the oil-producing delta region of the Nigerian federation.Keywords: Economic growth, import, export, oil trading products, premium motor spirit